2022
DOI: 10.3389/fbioe.2022.844200
|View full text |Cite
|
Sign up to set email alerts
|

System-Level Analysis of Transcriptional and Translational Regulatory Elements in Streptomyces griseus

Abstract: Bacteria belonging to Streptomyces have the ability to produce a wide range of secondary metabolites through a shift from primary to secondary metabolism regulated by complex networks activated after vegetative growth terminates. Despite considerable effort to understand the regulatory elements governing gene expression related to primary and secondary metabolism in Streptomyces, system-level information remains limited. In this study, we integrated four multi-omics datasets from Streptomyces griseus NBRC 1335… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…E. coli was observed to have much higher enrichment, while the highest was observed for the rest of the analyzed bacterial species. The rarity of the strong U-rich tracts in Streptomyces genomes was noted previously (1822). It has also been reported that terminators with U-rich tracts tend to terminate more strongly in S. avermitilis (18).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…E. coli was observed to have much higher enrichment, while the highest was observed for the rest of the analyzed bacterial species. The rarity of the strong U-rich tracts in Streptomyces genomes was noted previously (1822). It has also been reported that terminators with U-rich tracts tend to terminate more strongly in S. avermitilis (18).…”
Section: Discussionsupporting
confidence: 56%
“…In our analysis we included 691 and 957 intrinsic termination sites predicted by TERMITe in E. coli based on the data described in this study and Choe et al (17), respectively; 635, 1165, 984 and 1214 sites of B. subtilis based on data from Chhabra et al (15), Mandell et al (7), Dar et al (14) and Mondal et al (8), respectively; 796 terminators from E. faecalis (14); 862 terminators from L. monocytogenes (14); 206 terminators from Z. mobilis (24); 165 terminators from Synechocystis sp . (16); 629 terminators from S. coelicolor (20), 573 terminators from S. venezuelae (20); 520 terminators from S. tsukubensiis (20); 737 terminators from S. griseus (22); 495 terminators from S. lividans (20); 435 terminators from S. clavuligerus (21); 707 terminators from S. avermitilis (20) (Supplementary Figure 3A). All of the above-listed terminators have been identified using TERMITe as described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations